A randomized clinical trial to evaluate home‐based assessment of people over 75 years old. Issue 5 (11th March 2019) - Sano, Mary; Zhu, Carolyn W.; Kaye, Jeffrey; Mundt, James C.; Hayes, Tamara L.; Ferris, Steven; Thomas, Ronald G.; Sun, Chung‐Kai; Jiang, Yanxin; Donohue, Michael C.; Schneider, Lon S.; Egelko, Susan; et al.
Abstract: Introduction: There is an unmet need for effective methods for conducting dementia prevention trials. Methods: Home‐based assessment study compared feasibility and efficiency, ability to capture change over time using in‐home instruments, and ability to predict cognitive conversion using predefined triggers in a randomized clinical trial in (1) mail‐in questionnaire/live telephone interviews, (2) automated telephone/interactive voice recognition, and (3) internet‐based computer Kiosk technologies. Primary endpoint was defined as cognitive conversion. Results: Analysis followed a modified intent‐to‐treat principle. Dropout rates were low and similar across technologies but participants in Kiosk were more likely to dropout earlier. Staff resources needed were higher in Kiosk. In‐home instruments distinguished conversion and stable groups. Cognitively stable group showed improvement in cognitive measures. Triggering was associated with higher likelihood of conversion but statistically significant only in mail‐in questionnaire/live telephone interviews. Discussion: Relatively low efficiency of internet‐based assessment compared with testing by live‐assessors has implications for internet‐based recruitment and assessment efforts currently proposed for diverse populations.